The Biochemical Composition Of Seaweeds From The Persian Gulf And The Effect Of Seaweed Extract On The Growth And Biochemical Composition Of Microalgae Cultured As Live Food For Penaeus Indicus Larvae - Ghadikolaei, Kiuomars Rohani (2011)
The biochemical composition of three groups of seaweeds; green (Ulva lactuca and Enthromorpha intestinalis), brown (Sargassum illicifolium and Colpomenia sinuosa) and red (Hypnea valentiea and Gracilaria corticata) from the Persian Gulf and the effects of seaweed extracts (SWE) either as a supplement or as a substitute media to the f/2 medium on the growth and composition of two microalgae Isochrysis galbana and Chaetoceros muelleri cultured as live food for Penaeus indicus larvae were investigated.